Cold Regions Stability Test of Indirect Fire Artillery Weapons - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1976)
This TOP prescribes methods for determining the stability of indirect fire weapons fired from varied terrain types incurred in northern regions during the various seasons. Requirements for facilities and test instrumentation are included. Supersedes Rept. no. MTP-3-4-009 dated 22 Jul 70, AD-875 628.